Analysis and simulation of a blue energy cycle. (June 2016) - Sharma, K.; Kim, Y.-H.; Yiacoumi, S.; Gabitto, J.; Bilheux, H.Z.; Santodonato, L.J.; Mayes, R.T.; Dai, S.; Tsouris, C.
Abstract: The mixing process of fresh water and seawater releases a significant amount of energy and is a potential source of renewable energy. The so called 'blue energy' or salinity-gradient energy can be harvested by a device consisting of carbon electrodes immersed in an electrolyte solution, based on the principle of capacitive double layer expansion (CDLE). In this study, we have investigated the feasibility of energy production based on the CDLE principle. Experiments and computer simulations were used to study the process. Mesoporous carbon materials, synthesized at the Oak Ridge National Laboratory, were used as electrode materials in the experiments. Neutron imaging of the blue energy cycle was conducted with cylindrical mesoporous carbon electrodes and 0.5 M lithium chloride as the electrolyte solution. For experiments conducted at 0.6 V and 0.9 V applied potential, a voltage increase of 0.061 V and 0.054 V was observed, respectively. From sequences of neutron images obtained for each step of the blue energy cycle, information on the direction and magnitude of lithium ion transport was obtained. A computer code was developed to simulate the process. Experimental data and computer simulations allowed us to predict energy production. Graphical abstract: Neutron imaging experimental arrangement for blue energy experiments. Highlights: Salinity gradient energy is harnessed based on capacitive double-layer expansion. Neutron imaging revealed ion transport phenomena during blue energy cycle. Information from neutron imaging can be utilized to improve blue energy harvesting. Reducing the salinity resulted in a potential increase during the blue energy cycle.